2021
DOI: 10.1177/09721509211036798
|View full text |Cite
|
Sign up to set email alerts
|

Do Market Conditions Affect the Tracking Efficiency of Exchange-traded Funds? Evidence from Developed and Emerging Markets

Abstract: This study examines the tracking efficiency of a sample of exchange-traded funds (ETFs) from seven different emerging and developed markets, in bullish and bearish market conditions, using the data from daily closing prices. It seeks to address two major questions. First, do ETFs from both developed and emerging markets have the same behaviour regarding tracking their underlying indexes? Second, is ETFs tracking ability affected by events that could change market conditions from a bullish to a bearish pattern,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…They discovered non-trivial T.E.s and concluded that ETFs had significantly less exposure to the underlying indexes than their stated purpose. Neto et al 35 compared the tracking efficiency of developed and emerging markets. They discovered that developing markets had more significant tracking errors, particularly during bearish market regimes, whereas emerging markets had the opposite.…”
Section: Tracking Efficiencymentioning
confidence: 99%
“…They discovered non-trivial T.E.s and concluded that ETFs had significantly less exposure to the underlying indexes than their stated purpose. Neto et al 35 compared the tracking efficiency of developed and emerging markets. They discovered that developing markets had more significant tracking errors, particularly during bearish market regimes, whereas emerging markets had the opposite.…”
Section: Tracking Efficiencymentioning
confidence: 99%